2019
DOI: 10.26508/lsa.201900296
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive STAT5 activation regulates Paneth and Paneth-like cells to control Clostridium difficile colitis

Abstract: Clostridium difficile impairs Paneth cells, driving intestinal inflammation that exaggerates colitis. Besides secreting bactericidal products to restrain C. difficile, Paneth cells act as guardians that constitute a niche for intestinal epithelial stem cell (IESC) regeneration. However, how IESCs are sustained to specify Paneth-like cells as their niche remains unclear. Cytokine-JAK-STATs are required for IESC regeneration. We investigated how constitutive STAT5 activation (Ca-pYSTAT5) restricts IESC different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 78 publications
(156 reference statements)
1
21
0
Order By: Relevance
“…difficile infection is also associated with increased mucosal levels of pro-inflammatory cytokines (i.e., IFN-γ and TNF-α), which are capable of disrupting TJ and epithelial integrity in organoids as for C . difficile toxins [ 96 ]. Host STAT5-dependent JAK2 signaling pathway is necessary to initiate the production of anti-inflammatory cytokines and to promote intestinal epithelium repair.…”
Section: Components Of the Intestinal Barriermentioning
confidence: 99%
“…difficile infection is also associated with increased mucosal levels of pro-inflammatory cytokines (i.e., IFN-γ and TNF-α), which are capable of disrupting TJ and epithelial integrity in organoids as for C . difficile toxins [ 96 ]. Host STAT5-dependent JAK2 signaling pathway is necessary to initiate the production of anti-inflammatory cytokines and to promote intestinal epithelium repair.…”
Section: Components Of the Intestinal Barriermentioning
confidence: 99%
“…The IL-22/ Stat3 pathway can improve PC function by increasing the protein levels of lysozyme, RegIIIγ and α-cryptdin 5 under parenteral nutrition [119]. The IL-4 treatment can significantly decrease the gene expression levels of Paneth cell marker LYZ and reduce the proliferation of ISCs [120]. In addition, the IκB kinase (IKK)-NF-κB signalling pathway is involved in inflammatory process when its activation caused the depletion of PCs [121].…”
Section: Growth Factor-mediated Signalling Pathways Regulate the Devementioning
confidence: 99%
“…Multiple pathways, including the Wnt/β-catenin pathway and the expression of their target genes, are essential for maintaining epithelial barrier function and epithelial cell repair after injury. In C. difficile infection, the accumulation of TcdA and TcdB is associated with Wnt/β-catenin pathway inhibition, although this downregulation is induced, at least in part, by different mechanisms, and together with pro-inflammatory cytokine production within the intestinal mucosa, this accumulation likely results in intestinal epithelial stem cell niche degeneration and suppression of repair ( Farin et al, 2014 ; Leslie et al, 2015 ; Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, increased Wnt3a expression was found in patients with ulcerative colitis compared to the level found in patients with noninflammatory bowel disease, but no difference was found in the expression of a panel of Wnt target genes ( You et al, 2008 ). Although Paneth cells are an important source of Wnt ligands (Wnt3a) needed to sustain the self-renewal of intestinal epithelial stem cells, Paneth cells are impaired upon C. difficile infection ( Liu et al, 2019 ). In the present study, the expression of Wnt3a was found mainly in lamina propria cells, suggesting that immune-induced inflammatory cells are involved in the release of Wnt3a.…”
Section: Discussionmentioning
confidence: 99%